Eddy Surface Characteristics and Vertical Structure in the Gulf of Mexico from Satellite Observations and Model Simulations. Issue 2 (18th February 2020) - Brokaw, Richard J.; Subrahmanyam, Bulusu; Trott, Corinne B.; Chaigneau, Alexis
Abstract: The Gulf of Mexico exhibits strong circulation due to the Loop Current System, along with high mesoscale eddy activity. In order to investigate eddy characteristics, we apply an automatic eddy‐tracking algorithm to absolute dynamic topography maps and analyze the spatial distribution and evolution of eddy attributes including amplitude, radius, and eddy kinetic energy. The Loop Current region in the eastern Gulf of Mexico is an area of robust eddy generation for both cyclonic and anticyclonic eddies. Anticyclonic eddies were generally characterized by smaller amplitudes and larger radii when compared to their cyclonic counterparts. We also examine eddy surface properties including temperature and salinity anomalies as well as chlorophyll‐a concentration and observe how these properties vary between the eastern and western Gulf of Mexico. Persistent features such as the Loop Current System and coastal low‐salinity, highly biologically productive waters dominate eddy properties in the eastern side of the basin. We also apply the eddy‐tracking algorithm to a regional Hybrid Coordinate Ocean Model validated using Argo floats. We find that this model accurately reflects surface characteristics in the mesoscale eddy field as well as the mean vertical eddy structure and use it to extend our analysis of eddy properties with depth. We find that subsurface characteristics of density, salinity, temperature, and velocities vary greatly between eddies in the eastern and western Gulf of Mexico. Through composite analysis of both surface and subsurface eddy properties, we gain a more complete picture of the mechanisms behind the observable characteristics of these eddies. Plain Language Summary: The Gulf of Mexico's surface circulation is dominated by the large‐scale Loop Current System and mesoscale eddies. We apply an automatic eddy‐tracking algorithm to absolute dynamic topography in the Gulf of Mexico. This algorithm aids in analyzing the spatial variability in eddy physical characteristics such as amplitude, radius, and eddy kinetic energy. We also observe the surface and subsurface properties of salinity, temperature, and chlorophyll‐a concentration of these eddies and their surrounding waters. By separating the eddies based on circulation type (anticyclonic or cyclonic) and observing the depth structure of these eddies, we can better understand their dynamical characteristics. We also separate eddies based on their location in either the western or eastern Gulf. We find that the climatological features of the Loop Current and riverine discharge heavily affect eddy properties. This is seen in major differences in the temperature and salinity surface properties, as well as the vertical structure of eddies between the western and eastern Gulf of Mexico. Key Points: An eddy‐tracking algorithm was applied in the Gulf of Mexico to examine biophysical characteristics Composites of anticyclonic and cyclonic eddies show surface and subsurface characteristics and vertical eddy structure Eddy properties vary between the eastern and western Gulf of Mexico due to air‐sea interaction and differing long‐term gradients